Ride sync integration - Egill Þór Olgeirsson 2000-; Einar Tómas Grétarsson 2001-; Sigurður Valur Ásbjarnarsson 2002- (2024)
This is the final report and user manual for the Ride Sync Integration project for Swipe&Ride. Swipe&Ride is a project aimed at improving transportation with a mix of ridesharing and ride-hailing, combined with social media features. The project created a working model that includes signing up, managing profiles, switching between being a driver or passenger, and making ride requests. The app suggests rides based on time and place, and users can swipe to accept or decline. Developed by three computer science students from Reykjavík University, the project had some challenges with time management and completing features but succeeded in teamwork and making progress.